Isolation and immunocharacterization of lactobacillus salivarius from the intestine of wakame-fed pigs to develop novel "Immunosynbiotics" - Masumizu, Yuki (2019)
Emerging threats of antimicrobial resistance necessitate the exploration of effective alternatives for healthy livestock growth strategies. ?Immunosynbiotics?, a combination of immunoregulatory probiotics and prebiotics with synergistic effects when used together in feed, would be one of the most promising candidates. Lactobacilli are normal residents of the gastrointestinal tract of pigs, and many of them are able to exert beneficial immunoregulatory properties. On the other hand, wakame (Undaria pinnafida), an edible seaweed, has the potential to be used as an immunoregulatory prebiotic when added to livestock feed. Therefore, in order to develop a novel immunosynbiotic, we isolated and characterized immunoregulatory lactobacilli with the ability to utilize wakame. Following a month-long in vivo wakame feeding trial in 8-week-old Landrace pigs (n = 6), sections of intestinal mucous membrane were processed for bacteriological culture and followed by identification of pure colonies by 16S rRNA sequence. Each isolate was characterized in vitro in terms of their ability to assimilate to the wakame and to differentially modulate the expression of interleukin-6 (IL-6) and interferon beta (IFN-β) in the porcine intestinal epithelial (PIE) cells triggered by Toll-like receptor (TLR)-4 and TLR-3 activation, respectively. We demonstrated that feeding wakame to pigs significantly increased the lactobacilli population in the small intestine. We established a wakame-component adjusted culture media that allowed the isolation and characterization of a total of 128 Lactobacilli salivarius colonies from the gut of wakame-fed pigs. Interestingly, several L. salivarius isolates showed both high wakame assimilation ability and immunomodulatory capacities. Among the wakame assimilating isolates, L. salivarius FFIG71 showed a significantly higher capacity to upregulate the IL-6 expression, and L. salivarius FFIG131 showed significantly higher capacity to upregulate the IFN-β expression; these could be used as immunobiotic strains in combination with wakame for the development of novel immunologically active feeds for pigs.